The Genetic Architecture for Phenotypic Plasticity of the Rice Grain Ionome - Tan, Yongjun; Zhou, Jieqiang; Wang, Jiurong; Sun, Liang (Frontiers in Plant Science, 2020)
The ionome of the rice grain is crucial for the health of populations that consume rice as a staple food. However, the contribution of phenotypic plasticity to the variation of rice grain ionome and the genetic architecture of phenotypic plasticity are poorly understood. In this study, we investigated the rice grain ionome in a rice diversity panel that was grown in up to eight environments. We found that a considerable proportion of the ionome variance can be attributed to the phenotypic plasticity, which is under genetic control. A significant correlation between the mean phenotype and the phenotypic plasticity was detected. However, the genetic architecture for the mean phenotype was largely distinct from those for phenotypic plasticity. Also, the correlation between them was mainly attributed to the phenotypic divergence between rice subspecies. Furthermore, the results of whole-genome regression analysis showed that the genetic loci related to the phenotypic plasticity also explained a considerable proportion of the phenotypic variance in some environments, especially for the elements Cd, Cu, Mn, and Zn. Our study not only sheds light on the genetic architecture of phenotypic plasticity of the rice grain ionome but also suggests that the genetic loci related to phenotypic plasticity are valuable in rice grain ionome improvement breeding.